Polymeric Nanoparticles for Mitochondria Targeting Mediated Robust Cancer Therapy - Sun, Yajing; Yang, Qingshan; Xia, Xue; Li, Xiaozhe; Ruan, Weimin; Zheng, Meng; Zou, Yan; Shi, Bingyang (Frontiers in Bioengineering and Biotechnology, 2021)
Despite all sorts of innovations in medical researches over the past decades, cancer remains a major threat to human health. Mitochondria is an essential organelle in eukaryotic cells, and their dysfunctions contribute to numerous diseases including cancers. Mitochondria-targeted cancer therapy, which specifically delivers drugs into mitochondria, is a promising strategy for enhancing anticancer treatment efficiency. However, owing to their special double and hydrophobic membrane system as well as highly negative potentials, mitochondria remains a challenging target for therapeutic agents to reach and access. Polymeric nanoparticles exceeded in cancer therapy ascribe to their unique features including ideal biocompatible, readily design and synthesis, as well as flexible ligand decoration. Significant efforts have been put forward to develop mitochondria-targeted polymeric nanoparticles. In this review, we focus on the smart design of polymeric nanosystems for mitochondria targeting and summarized the current applications in improving cancer therapy.